ҚОЙ ҰЛПАЛАРЫНДАҒЫ ПРОСТАГЛАНДИН Н СИТАЗАНЫҢ СИПАТТАМАСЫ (Experimental biology, 2015)
The kinetic properties of peroxides activity of the first enzyme of of muscel , periferical blood, kidney and heart cell were investigated and researched leaven of aspirin and yndometacyn for prostaglandin synthase system. The PGH synthase of musel and heart cell have also isoforme, periferical blood and kidney too.